Resource Use Efficiency in Cultivation of Major Food Crops under Rainfed and Irrigated Conditions in Northern Dry Zone of Karnataka - K. S., Rashmi; T. N., Prakash Kammardi; Bi., Afrin Zainb; K. R., Hamsa (International Journal of Bio-resource and Stress Management, 2017)
The study is on resource use efficiency of the major rainfed and irrigated crops in Northern dry zone (NDZ) of Karnataka, India in 2013−14. Bagalkot district was selected as a representative of Northern dry zone of Karnataka. The random sample of 90 farmers was chosen, 30 each belongs to cultivation under borewell irrigation, canal irrigation and rainfed condition, respectively. Cobb-Douglas production function was employed to assess the resource use efficiency in sugarcane under both borewell and canal irrigation and greengram under rainfed condition. DEA (Data envelope analysis) was used to find out the farm efficiencies of farmers in irrigated sugarcane, onion under borewell irrigation, sorghum and greengram were considered under rainfed condition for the analysis. The results indicated that MVP (Marginal value product) /MFC (Marginal factor cost) ratio for groundwater was less than one showed that there is no scope for further use of groundwater in the case of sugarcane under borewell irrigation. There is no scope for further use of human labour as ratio less than one in sugarcane under canal irrigation cultivation. While, in the case of rainfed greengram results depict that inefficient use of inputs such as fertilizers, human labour, seeds. DEA results represents that allocative efficiency of farmers in the study area were less than their technical efficiency. Therefore, this study concluded that there is a need to reallocate the resource in major crop cultivation in the study area and extension efforts has to initiate to guide farmers in order to increase their allocative efficiency with technical efficiency.